Design Principles and Mechanistic Understandings of Non-Noble-Metal Bifunctional Electrocatalysts for Zinc–Air Batteries - Gao, Yunnan; Liu, Ling; Jiang, Yi; Yu, Dexin; Zheng, Xiaomei; Wang, Jiayi; Liu, Jingwei; Luo, Dan; Zhang, Yongguang; Shi, Zhenjia; Wang, Xin; Deng, Ya‑Ping; et al. (Nano-Micro Letters, 2024)
Zinc–air batteries (ZABs) are promising energy storage systems because of high theoretical energy density, safety, low cost, and abundance of zinc. However, the slow multi-step reaction of oxygen and heavy reliance on noble-metal catalysts hinder the practical applications of ZABs. Therefore, feasible and advanced non-noble-metal electrocatalysts for air cathodes need to be identified to promote the oxygen catalytic reaction. In this review, we initially introduced the advancement of ZABs in the past two decades and provided an overview of key developments in this field. Then, we discussed the working mechanism and the design of bifunctional electrocatalysts from the perspective of morphology design, crystal structure tuning, interface strategy, and atomic engineering. We also included theoretical studies, machine learning, and advanced characterization technologies to provide a comprehensive understanding of the structure-performance relationship of electrocatalysts and the reaction pathways of the oxygen redox reactions. Finally, we discussed the challenges and prospects related to designing advanced non-noble-metal bifunctional electrocatalysts for ZABs. Highlights: 1 The recent advances in non-noble-metal bifunctional electrocatalysts for zinc–air batteries are summarized with the design principles. 2 The working mechanism are discussed to provide a comprehensive understanding of the structure-performance relationship of electrocatalysts and the reaction pathways of the oxygen redox reactions. 3 The challenges and prospects related to designing advanced non-noble-metal bifunctional electrocatalysts for high performance zinc–air batteries are provided.